2002
DOI: 10.2223/jped.820
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis: clinical and laboratorial aspects

Abstract: Objective: to compare the clinical and laboratorial data before and after the treatment of patients with visceral leishmaniasis admitted to a pediatric hospital in a nonendemic area, highlighting the importance of recognizing visceral leishmaniasis in pediatric patients.Methods: clinical, laboratorial and treatment data of 78 patients with visceral leishmaniasis were evaluated from 1981 to 1992. We analyzed the average level of hemoglobin, leukocyte, neutrophil, platelet, albumin, gammaglobulin, class and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 15 publications
(17 reference statements)
3
20
0
16
Order By: Relevance
“…The main clinical symptoms and signs presented at the initial evaluation were: fever (97%), splenomegaly (96.4%), weight loss (95.5%), pallor (93.6%), cough (89.7%), hepatomegaly (87.2%), asthenia (83.3%), anorexia (82.9%) and vomiting (73.9%) (Figure 1). year in Brazil [5,6,9,10]. All over the world, about 200 million people are at risk [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main clinical symptoms and signs presented at the initial evaluation were: fever (97%), splenomegaly (96.4%), weight loss (95.5%), pallor (93.6%), cough (89.7%), hepatomegaly (87.2%), asthenia (83.3%), anorexia (82.9%) and vomiting (73.9%) (Figure 1). year in Brazil [5,6,9,10]. All over the world, about 200 million people are at risk [4].…”
Section: Resultsmentioning
confidence: 99%
“…The main clinical manifestations among our patients were fever, splenomegaly, weight loss, pallor, cough, hepatomegaly, asthenia, anorexia and vomiting. In recent Brazilian studies of 78 to 530 patients with visceral leishmaniasis, the main signs and symptoms presented were hepatomegaly (77%-100%), pallor (98%), fever (94%-96%), splenomegaly (77%-100%), lymphadenopathy (86%), abdominal volume increase (72%-82%), eyelash growth (74%), dry hair (73%), weight loss (69%-71%), anemia (69%), asthenia (59%-66%), anorexia (38%-61%), cough (30%), hemorrhage manifestations (10%-28%), nausea/vomiting (27%), myalgia (19%), headache (19%), diarrhea (19%), edema (14%-17%) dry skin (12%) and jaundice (6%) [9,12,13]. This demonstrates the large spectrum of clinical manifestations that can be seen in visceral leishmaniasis.…”
Section: Resultsmentioning
confidence: 99%
“…This male gender preponderance, particularly among children, has also been reported from South America. 25 However; the underlying aetiology of this VL feature is not fully understood. A study from Brazil has suggested a hormonal factor to be linked with this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VL in pediatric population is high due to the higher susceptibility to infections and the immune-depressed state found in this population [6]. The majority of pediatric patients present with fever, anemia, hepatosplenomegaly, weight loss, haemorrhage, lymphadenopathy and less frequently dry cough and diarrhea [7].…”
Section: Introductionmentioning
confidence: 99%